Migrants from Ukraine as an answer to the needs of the Polish labour market - the perspective of border enterprises - Zabielska, Izabela; Kowalewska, Grażyna (Ekonomia i Prawo. Economics and Law, 2026)
Motivation: Russia’s war against Ukraine triggered a sharp rise in cross-border mobility across Europe. Neighbouring states at the EU’s periphery absorbed substantial inflows, offering safety and socio-economic stability to displaced Ukrainians. For host economies, this coincided with acute labour shortages, enabling employers to stabilise staffing while host states gained predominantly working-age residents. Aim: The main objective of the study was to determine whether the employment of migrant workers, especially from Ukraine, contributes to closing gaps in the labour markets in specific industries in Poland's border regions/voivodeships. Results: We developed an original dual profile capturing (1) the migrant/refugee entering the labour market and (2) the employer hiring them given sectoral needs and organisational capacity. Descriptive evidence shows that over half of firms operate locally, one-third nationally, 10% within the EU market, 5% across Europe, and 2% are globally oriented. Migrants are most frequently employed in construction, hospitality, retail/wholesale, and services. In over 50% of firms, migrants work more than 40 hours per week. 76% of employers expect an improved output-to-input (productivity) ratio following recruitment. The most salient enablers are economic instruments, notably greater access to national and EU funding - subsidies, tax relief, co-financed training. These results add value by providing firm-level evidence from border regions—an under-researched context—linking employers’ demand with migrant integration and highlighting institutional infrastructures - qualification recognition, skills databases as decisive complements to short-term administrative simplification.